Helium permeability of high-performance SiC/SiC tube. Issue 12 (1st December 2016) - Hayasaka, Daisuke; Kishimoto, Hirotatsu; Kohyama, Akira
ABSTRACT: SiC/SiC tubes for high temperature systems, such as, fuel cladding and heat exchanger, have been intensively developed. However, representing international R & D activities concluded gas tight SiC/SiC tube fabrication is not realistic. Based on the long R & D efforts, DEMO-NITE process has presented excellent helium leak tightness better than ever expected. These accomplishments make one of the NITE products as highly attractive nuclear fuel cladding. Followed to the experimental method of helium permeability measurement and its results, generation-wise improvements, and related microstructural features are presented.